Pembelajaran IPS dalam Kurikulum Merdeka Tingkat Satuan Pendidikan SD, SMP, dan SMA - Rohaeni, Mira; Mustofa, Riri Gustiana; Prasetyo, Septio Aji; Nurhasanah, Vania Putri; Sudrajat, Yayan (PT. Lancar Media Komunikasi, 2025)
The Merdeka Belajar curriculum is here to be the answer to the tight com-petition of human resources in the world in the 21st century. The change in curriculum to an independent curriculum also affects social studies learning in elementary, junior high, high school. This research method uses descrip-tive qualitative research methods, while data collection techniques use lit-erature study studies, namely studies that have the aim of collecting various data and information needed for research. The results of the discussion ob-tained similarities and differences from social studies learning activities in the independent curriculum from elementary, junior high, and high school levels. Unlike social studies learning in junior high and high school, the learning process is carried out through activities such as showing relation-ships, using various studies, analyzing, critiquing, applying thoughts and values, designing, applying, constructing, developing, and most importantly the learning process is directed so that students can integrate various basic concepts of social science through learning principles that liberate and give freedom in thinking.